The Impact of Anesthetic Modality Selection on Surgical Outcomes in Trauma Management - Nowak, Anna; Dudziak, Piotr; Golińska, Maria; Maj, Wojciech; Łyko, Mateusz; Kurasz, Jakub; Siudziński, Paweł; Skoczylas, Alicja; Tomaszewska, Wiktoria; Pala, Katarzyna; et al. (Quality in Sport, 2025)
The selection of anesthesia during surgical management of injuries is of paramount importance in ensuring patient comfort, procedural safety, and optimal surgical outcomes. The determination of the anesthetic modality is made by the anesthesiologist in consultation with the surgical team, taking into consideration the patient’s medical status, the nature and extent of the injury, the anticipated duration of the procedure, and, when feasible, the patient’s preferences.